Improving the Solubility of Artificial Ligands of Streptavidin to Enable More Practical Reversible Switching of Protein Localization in Cells. (3rd January 2017) - Tachibana, Ryo; Terai, Takuya; Boncompain, Gaelle; Sugiyama, Shigeru; Saito, Nae; Perez, Franck; Urano, Yasuteru
Abstract: Chemical inducers that can control target‐protein localization in living cells are powerful tools to investigate dynamic biological systems. We recently reported the retention using selective hook or "RUSH" system for reversible localization change of proteins of interest by addition/washout of small‐molecule artificial ligands of streptavidin (ALiS). However, the utility of previously developed ALiS was restricted by limited solubility in water. Here, we overcame this problem by X‐ray crystal structure‐guided design of a more soluble ALiS derivative (ALiS‐3), which retains sufficient streptavidin‐binding affinity for use in the RUSH system. The ALiS‐3–streptavidin interaction was characterized in detail. ALiS‐3 is a convenient and effective tool for dynamic control of α‐mannosidase II localization between ER and Golgi in living cells. Abstract : ALiS springs into action : A novel artificial ligand for streptavidin, ALiS‐3, which exhibits sufficient solubility as well as streptavidin‐binding affinity for use in the RUSH (retention using selective hook) system. The ALiS‐3–streptavidin interaction was characterized in detail, and its utility was confirmed by cell experiments.